The efficacy of a low-dose combination of febuxostat and benzbromarone versus each drug used alone for the treatment of gout - Zheng, Caiyu; Tong, Qingwen; Zhang, Zhijun; Lin, Chunmei; Wang, Zhiyi; Kang, Dongshu; Lin, Yanmei; Tian, Jianqing (Frontiers in Medicine, 2025)
ObjectiveThe study focuses on comparing the efficacy of a low-dose combination of febuxostat and benzbromarone versus each drug used alone for the treatment of gout.MethodsA prospective, randomized, open-labeled trial of men with gout and renal uric acid underexcretion was conducted. We randomly assigned 100 patients to either low-dose febuxostat or low-dose benzbromarone for initial treatment. 43 patients with complete data were analyzed in this study. The analysis of medication Treatment effects, Period effects and Patient-Within-Sequence effects for different treatment options was performed by cross-test ANOVA.ResultThe cross-trial analysis revealed no significant differences in the magnitude of uric acid decline among the three groups after treatment. Similarly, there were no statistically significant differences in blood lipid levels, CRP, CA724, eGFR, and ALT among the three groups post-treatment. The null model without participant-specific benefits was a linear mixed model for ALT, AST, eGFR, TC, TG, LDL, UA, CRP, CA724, and 24-h uric acid with age, BMI, treatment period and treatment as fixed factors, and the intercept as a random factor by participant. The results indicated no significant differences on relevant indicators among the three treatment regimens.ConclusionOur study did not identify a difference in the efficacy of reducing uric acid excretion in gout patients when comparing conventional dose febuxostat and benzbromarone monotherapy versus low-dose combination therapy.